The Nigerian Civil War, 1967-1970 : history and reminiscences - Momoh, H. B. (Ibadan : Sam Bookman Publishers, 2000)
This volume represents an account of the Nigerian civil war 1967-1970. It also includes interviews of army officers who served during the war.
Includes bibliographical references (p. 931-932) and index.
lje 19/3/19
Arch
Keywords: Civil War (Nigeria : 1967-1970); Civil war; Nigeria